Ecological-Economic Fisheries Management Advice—Quantification of Potential Benefits for the Case of the Eastern Baltic COD Fishery - Voss, Rudi; Quaas, Martin F.; Stoeven, Max T.; Schmidt, Jörn O.; Tomczak, Maciej T.; Möllmann, Christian (Frontiers in Marine Science, 2017)
Fishing is a social and economic activity, and consequently socio-economic considerations are important for resource management. While this is acknowledged in the theory of Ecosystem-Based Management (EBM) and its sector-specific development Ecosystem-Based Fisheries Management (EBFM), currently applied fishery management objectives often ignore economic considerations. Year-to-year management, however, implicitly responds to short-term economic interests, and consequently, regularly resorts to tactical short-term rather than strategic long-term decisions. The aim of this article is to introduce a new way of estimating management advice referred to as an ‘ecologically-constrained Maximum Economic Yield’ (eMEY) strategy, which takes into account ecological criteria as well as short- to medium-term economic costs. We further illustrate what net cost reductions per year are possible applying the eMEY strategy compared with the existing way of setting total allowable catches (TACs). The eMEY approach aims at maximizing the economic benefits for the fishery as well as society (consumers), while safeguarding precautionary stock sizes. Using an age-structured optimization model parameterized for the Eastern Baltic cod case study, we find that application of eMEY advice results in more stability in catch advice. Quantification and visualization of the costs of deviating from eMEY advice offers a transparent basis for evaluating decision-making outcomes. The costs of overfishing are mainly borne by the commercial fishery, while fishing less than optimal is particularly costly for the processing industry and consumers. To foster the uptake of our eMEY approach in current advice given by the International Council for the Exploration of the Sea (ICES) and the EU fishery management system, we suggest an easy-to-implement scheme of providing integrated advice, also accounting for economic considerations.